Proximity matters: exploring relationships among neighborhoods, congregations, and the residential patterns of members - Sinha, Jill Witmer; Hillier, Amy; Cnaan, Ram A.; MacGrew, Charlene (Journal for the scientific study of religion, 2007)
Using the Philadelphia Congregation Census, the Neighborhood Change Database, the U.S. Census , and geographic information systems (GIS) software, this study compared characteristics of congregations made up of members who live nearby their congregation's building to those with more members who commute from outside the immediate area or outside the city. We considered whether the neighborhood characteristics in which the "commuter" versus " resident" congregations were located differed in regard to racial composition, socioeconomic status, and residential stability. The study found that where the pastor lives in relation to the building, denomination, racial composition of membership, and the stability of the neighborhood were related to members' residential proximity to the congregation building.